Do our engineering students have what it takes? : the critical thinking skills - Ramlan, Ramlan (Kolej Sains dan Teknologi, 2007)
highlighted issues was the perception from many parties that our graduates were not able to think critically. But that statement was merely a statement that has been blown out of proportion. As to date, there was a great shortage in researches that thoroughly looks into university students critical thinking ability, and produces a result that can authenticate the statement that Malaysian graduates are not critical thinkers. The aim of this paper is therefore to look at how the Rasch Model will be able to facilitate the validity process in an effort to measure critical thinking aptitude in a multiracial, multi religion and multilingual society in a developing country in South East Asia like Malaysia. The instrument used for this research was adapted and translated from William Critical Thinking Assessment (Williams CTA, 2002). The CTA was designed to measure 4 sub-constructs: analysis, evaluation, inferences and interpretation. This instrument was claimed to be unidimensional and comprise a single factor, and the most recent Cronbach Alpha Coefficient was contended to be between .80 and .83 (William, 2002). The definition guiding the development of the instrument is based on the Delphi Mode l(Facione, 1992). Data collection were analyzed based on the Rasch Model for dichotomous data using the computer application, WINSTEPS version3.57.3 (Linacre). In addition, the data were also analyzed using SPSS version 11.5. The sample consisted of 567(2nd and 3rd Year) students representing students from 12 different courses from two public universities. The result shows that the instrument has very high item separation reliability (0.99). However, person separation reliability is too low (.14). On the whole, the students critical thinking aptitude seems to be at a low level too. Are these supposedly selected students unable to think critically then? Are we using the correct measurement tool? This paper will answer this question.